Pengaruh Sistem Pembayaran Digital terhadap Efektivitas dan Efisiensi Penjualan di PT Sumber Alfariya Trijaya Tbk - Oktaria, Eka Travilta; Hermansyah, Hermansyah (Penerbit Goodwood, 2023)
Purpose: This study aims to analyze the effect of the digital payment system on the effectiveness and efficiency of sales at PT Sumber Alfariya Trijaya Tbk Lampung branch. Method: The research method used in this study is a quantitative method with an observation approach. Data collection techniques based on primary data sources, in this study using the questionnaire method. The analysis technique used in this research is validity test, reliability test, classical assumption test, simple linear regression analysis, coefficient of determination, and t test. Result: Digital payment systems have a significant effect on the effectiveness and efficiency of sales and have a 60% influence on the effectiveness and efficiency of a company's sales PT Sumber Alfariya Trijaya Tbk Lampung Branch. Limitation: In the research that has been done there are research limitations which in this case affect the results of this study, namely the answers from respondents when filling out the questionnaire that are not in accordance with the problems faced, this is due to differences in income and understanding of each respondent Contribution: Based on the research that has been done that the digital payment system has an influence on the effectiveness and efficiency of sales, so it is recommended for companies to continue to develop this digital payment system so that the system runs accurately, faster and more efficiently. Novelty: The novelty of this research is the use of payment systems that are starting to change a lot, not only with new designs, but what is being studied is a phenomenon that has already occurred, namely the transfer from paper money to digital money.